Confidentiality & record keeping in counselling & psychotherapy Legal resources for counsellors and psychotherapists - Mitchels Barbara; Trefgarne Sursannah (ed); Mitchels Barbara (London SAGE Publications, 2021)
Confidentially and disclosures:Information Sharing